Step-by-step reduction of travertine porosity using low soluble inorganic salts - Terziu, Rihana; Dauti, Mihane; Xhaxhiu, Kledi; Baraj, Edlira (Journal of Metallomics and Nanotechnologies, 2016)
In the present study the treatment by three chemical solutions (5%) of travertine is considered. The overall process assumes the structural pore reduction due to the continuous controlled crystallization of low soluble inorganic salts such as calcium sulfate and calcium oxalate. Travertine samples of monolithic blocks of Turkish origin previously cut in form of parallelepiped blocs with length of 25 ± 1mm, width and thickness of 7 mm are employed in this study. The prepared samples were dipped in distilled water for 2-3 hours followed by drying up to 6 hours at 70 °C, 6 hours at 100 °C and 12 hours to 125 °C. Consolidation of travertine samples is carried out by treatment in three stages: the first stage involves treatment with calcium acetate (Ca(CH3COO)2• H2O), the second stage involves the treatment with ammonium sulphate (NH4)2SO4 followed by the third stage includes the treatment with ammonium oxalate (NH4)2C2O4•H2O. The decreasing of porosity and surface area is monitored by continuous gravimetric measurements followed by gas- and mercury porosimetry measurements. After each treatment, the sample weight increases and its porosity decreases. All samples were subject of: 10, 20, 30, 40, 50 treatments respectively.
Keywords: sírany; povrchové vlastnosti; Crystallization; travertin; testování materiálů; minerály; Surface Properties; Materials Testing; Minerals; Calcium Sulfate; šťavelan vápenatý; Sulfates; Oxalic Acid; krystalizace; síran vápenatý; kyselina oxalová; Calcium Oxalate